URGENSI PELIBATAN DAN PARTISIPASI MASYARAKAT DALAM PENGAWASAN PENYELENGGARAAN PEMILU SERENTAK TAHUN 2024 - Dairani; Trinah Asi Islami (YUSTISIA MERDEKA : Jurnal Ilmiah Hukum, 2023)
Simultaneous elections in 2024 will soon take place, this is marked by the start of several election stages starting from the formation of election commissions/organizers to the drawing of serial political party numbers. The holding of democratic elections in accordance with the principles of elections is a must to be realized, especially in the simultaneous elections in 2024. So that concrete efforts are needed in monitoring, overseeing and supervising and supporting stages by stages in the implementation of elections. Constitutionally, Bawaslu is an institution whose job is to supervise the implementation of elections. However, the involvement and participation of the public/community in terms of monitoring the implementation of elections is important to do by looking at the form, number and characteristics of massive and systematic violations. Public involvement is a constitutional right in overseeing and giving control over the holding of democratic elections in order to ensure people's sovereignty in the holding of elections. There are several important and crucial stages in the election stage, namely the collection of voter list data which is often found by fictitious voters and unregistered voters and the second crucial stage is the implementation of voting in the field. The 2024 simultaneous elections will be more complicated and take up a lot of time and energy so that the existence and involvement of the public/community in terms of oversight and monitoring functions is absolutely necessary in order to assist the Bawaslu in carrying out its duties and functions so that quality elections can be created with intelligent voters by being able to suppress and minimize the number of election violations.